Farrerol attenuates MPP+‐induced inflammatory response by TLR4 signaling in a microglia cell line. (8th February 2019) - Cui, Bei; Guo, Xiaqing; You, Yanhui; Fu, Rongli
Abstract : Farrerol was found to possess neuroprotective effect; however, the mechanism remains unknown. The aim of the present study was to explore the effect of farrerol on MPP + ‐induced inflammation in mouse microglial BV‐2 cells and to elaborate the underlying mechanism. MTT assay was performed to measure the cell viability. The pro‐inflammatory mediators and cytokines including interleukin (IL)‐6, IL‐1β, and tumor necrosis factor‐α (TNF‐α); inducible nitric oxide synthase; and cyclooxygenase 2 were measured. The expression of p‐p65, p‐IκBα, toll‐like receptor 4 (TLR4), and myeloid differentiation primary response 88 were analyzed by western blot. We found that farrerol treatment improved cell viability in MPP + ‐induced BV‐2 cells. MPP + ‐induced upregulation of IL‐6, IL‐1β, and TNF‐α was inhibited by farrerol treatment. Farrerol treatment also attenuated MPP + ‐induced expression of inducible nitric oxide synthase and cyclooxygenase 2 as well as the activation of NF‐κB in BV‐2 cells. MPP + ‐induced TLR4 signaling was markedly diminished by farrerol treatment. Knockdown of TLR4 attenuated MPP + ‐induced inflammatory response in BV‐2 cells. In conclusion, farrerol treatment attenuated MPP + ‐induced inflammatory response by inhibiting the TLR4 signaling pathway in BV‐2 cells. The results indicated that farrerol could be used as a therapeutic agent for preventing or alleviating the neuroinflammation‐related diseases, such as Parkinson's disease.